The Effect of Corporate Social Responsibility on The Financial Performance of Mining Companies Listed on The Indonesia Stock Exchange Period 2016-2020 - Yanti, Rafida; Suwarno, Suwarno (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
CSR is currently still a debate where CSR is said to be part of marketing or purely as a corporate social responsibility to the environment.This study aims to determine the effect of Corporate Social Responsibility on the Return On Assets (ROA) of mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Know the effect of Corporate Social Responsibility on the Return On Equity (ROE) of mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Know the effect of Corporate Social Responsibility on Price Book Value (PBV) of mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period.The research method used in this study is a quantitative method, while the data collection technique used is the library and documentation method. The data analysis technique in this research is using simple regression analysis. The results of this study indicate that it is simultaneously stated that the CSR variable (X), has implications for the variables ROA (Y1), ROE (Y2), PBV (Y3). it can be seen from the significant value on the ROA of 0.626 and the calculated F value of 0.239, and the significant value of the ROE of 0.745 and the Fcount of 0.106, it can be concluded that Ho is accepted and HỊ is rejected because the the significance value of F is greater than 0.05. While the significant value of PBV is 0.031 and F count is 4.816, it can be concluded that Ho is rejected and H1 is accepted because the significant value is less than 0.05. While partially the Corporate Social Responsibility variable has no effect on Return On Assets, Return On Equity, Price Book Value.